Organizational Behaviour - Judge, Timothy; Robbins, Stephen P.; Campbell, Timothy (Pearson International Content, 2017)
This second European edition of this classic textbook brings the exceptional introduction to organizational behaviour written by the masters of the subject, and adapts it to meet the needs of students studying in Europe today. Fully updated and revised, this adaptation continues the tradition of making current, relevant research come alive for students, while maintaining its hallmark features – clear writing style, cutting-edge content and compelling pedagogy. This new edition offers real-life examples drawn from a global range of organizations including Google, Cadbury, Apple, Capital One, Microsoft, Lego, Ferrari and more, plus up-to-date insights into the latest research and hot topics from across the world. Key features include: ‘Myth or science?’ boxes, which provide repeated evidence that common sense can often lead us astray in the attempt to understand human behaviour, and that behavioural research offers a means for testing the validity of common-sense notions. ‘OB in the news’ which prepares students to recognise and evaluate OB issues which often appear in the news when presented with them in newspapers, magazines, TV, etc. ‘Face the facts’: these boxes highlight interesting facts from recent surveys that emphasise key aspects of the text. For example, diversity across Europe, the extent of employee engagement, and the popularity of working in teams. "As a whole, the content of the book is strong, and is well-structured witha European focus.” Mohammad Lafiti,Uppsala University, Sweden